Use of Moringa oleifera Lam. seeds and their technological functions: a review - Nobre do Nascimento, Maria Eduarda; Santos, Tais Letícia Oliveira; Schmidt, Flávio Luis (Food Science and Technology, 2025)
Moringa oleifera Lam. is a plant known worldwide for its wide-ranging technological and medicinal uses, as well as for its high nutritional value found in various parts of the plant. This study aimed to compile information regarding the characteristics of proteins extracted from Moringa seeds through various methodologies and their applications. A considerable amount of protein was observed in the seeds, which can be extracted in different ways and shows potential for use in water treatment and important technological functions. Therefore, it can be inferred that the protein extracted from Moringa seeds has the potential to be further studied across different industrial sectors, with noteworthy potential for innovation in food industry processes and products.